Babae sa Breakwater - O'Hara, Mario; Luna, Katherine; Versoza, Gardo; Villame, Yoyoy (Entertainment Warehouse Production, 2004)
Basilio and Buboy, two boys from a Coastal town, sail off for Manila in search of a better life. Instead they find them selves squabbling for inhospitable space by the Breakwater of Manila Bay. Yet amid the rubbles of destitution Basilio finds redemption in Paguita a prostitute whose life is fueled mainly by drugs and alcohol. Basilio's affection sets Paquita on the road to recovery.